Characteristics of Catch Fisheries in Pangandaran District - Martin Anjar Ginanjar (Agrikan: Jurnal Agribisnis Perikanan, 2022)
The characteristics of fishing gear are important for sustainable capture fisheries management and development, with several assessments and observations on fishing gear construction, fishing operations and environmental friendly assessment of the fishing gear used by fishermen. One of the fishing gear that is widely used by fishermen in Pangandaran Regency is gillnet fishing gear. This study aims to identify the characteristics of gillnet fishing gear and test the level of environmental friendliness of gillnet fishing gear. The analytical method applied is descriptive analysis. The results of this study indicate that the characteristics of gillnet fishing gear in Pangandaran Regency are: webbing has a mesh size of 4 inches with a transparent color made of polyamide monofilament, targeting white pomfret. On average, gillnet fishermen have reached their productive age at work, and the vessels used are 1 GT in size and the quality of their catch is still fresh. The results of the analysis show that the gillnets in Pangandaran can be categorized as environmentally friendly fishing gear with a score of 27.9.